Fourier Method for an Existence of Quasilinear Inverse Pseudo-Parabolic Equation - Baglan, Irem; Kanca, Fatma; Mishra, Vishnu Narayan (Tarbiat Modares Univ, Acecr, 2024)
In this work, the inverse quasi -linear pseudo -parabolic problem was investigated. We demonstrated the solution by the Fourier approximation. The inverse problem was first examined by linearizing and then used implicit finite difference schema for the numerical solution.
Keywords: Pseudo-Parabolic Problem; Fourier Method; Nonlocal(Periodic) Boundary Condition; Implicit Method